Smartphone-based battery-free and flexible electrochemical patch for calcium and chloride ions detections in biofluids - Xu, Gang; Cheng, Chen; Yuan, Wei; Liu, Zhaoyang; Zhu, Lihang; Li, Xintong; Lu, Yanli; Chen, Zetao; Liu, Jinglong; Cui, Zheng; Liu, Jingjing; Men, Hong; et al. (Sensors and actuators. B, Chemical, 2019)
[Display omitted] •The electrochemical patch is totally battery-free and wireless, which enabled wireless power and data transmission with smartphones.•The printed stretchable electrode array could maintain stable conductivity during stretching, without serpentine designs.•The patch achieved quantitative detections of calcium and chloride ions in various biofluids.•The Ca2+ and Cl− sensors both showed high sensitivity, repeatability, selectivity, and long-time stability. Last decade has seen a growing trend toward smartphone-based biochemical sensing systems. Meanwhile, flexible electrochemical sensing devices like wristbands, patches, and tattoos have been widely developed for in situ detections of analytes in accessible biofluids. For these devices, the connectivity with smartphone and the flexibility of the whole device are hard to achieve at the same time, due to the need for rigid batteries or wired connections. Here, a smartphone-based battery-free and flexible electrochemical patch is developed for real-time calcium and chloride ions detections in various biofluids. The patch is integrated with near field communication (NFC) module, on-site signal processing circuitry, and an all-printed stretchable electrode array which can maintain stable conductivity during stretching, without the need for serpentine designs. The device enables wireless power harvesting, on-site signal processing, and wireless data transmission capabilities. NFC-enabled smartphones can wirelessly power the patch and get the detection results through inductive coupling between antennas. The calcium and chloride sensors showed good sensitivity, repeatability, selectivity, and stability in quantitative detections of target ions. Ex situ measurements in serum, urine, tear, and sweat demonstrated good consistency with specialized instrument. Real-time on-body sweat analysis with the patch was also performed, which further indicated the usability and stability of the device in wearable applications. This platform provides a battery-free, wireless, and flexible solution for smartphone-based electrochemical sensing systems, which can be applied to rapid analysis of various biofluids.